Study of high-resolution analysis of Rayleigh waves on the basis of the Choi–Williams distribution - Xiang, Min; Zhang, Xuhui; Wei, Yuxuan; Yao, Xiaoyong (Frontiers in Earth Science, 2025)
Rayleigh wave exploration is widely used in the field of engineering investigation, which can analyze the near surface velocity structure. However, the traditional Rayleigh wave exploration data processing method can only provide the average change of Rayleigh wave phase velocity with depth under the seismic line, but cannot obtain the horizontal change of Rayleigh wave phase velocity along the line direction, which brings great challenges to the detection of underground wave velocity anomalies. To solve these problems, the Choi‒Williams distribution is introduced to process Rayleigh waves, and the relationships among the Rayleigh wave time, frequency and amplitude are obtained. The frequency dispersion curve is subsequently calculated via similarity analysis. In this method, first, the Rayleigh wave is intercepted in the time domain. Second, the Choi‒Williams distribution of Rayleigh waves is calculated, and the time domain waveform of each frequency component of each Rayleigh wave is obtained. The time difference is subsequently calculated via similarity analysis, and the dispersion curve between two adjacent channels is obtained. Finally, the phase velocity image below the seismic arrangement is obtained via combination with the multichannel Rayleigh wave dispersion curve. When this method is applied to the detection of geological anomalies in engineering investigations, it can accurately reflect the spatial distribution position of the detection target and has a relatively high lateral resolution.